1999
DOI: 10.1021/la990231n
|View full text |Cite
|
Sign up to set email alerts
|

Water Vapor Adsorption on the SiO2−CaCl2 Sol−Gel Composites

Abstract: The sol−gel adsorbents of water vapor composed of silica and calcium chloride exhibit fairly stable properties during at least one hundred adsorption−desorption cycles, with sorption capacities ca. 1 kg of water/kg of adsorbent. These materials can be regenerated by heating at 200 °C. In the relative pressure range 0−0.25 water adsorption can be effectively portrayed using the Dubinin−Astakhov equation. Investigations tend to indicate that the multilayer mechanism of water adsorption, boosted by a synergistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 24 publications
3
6
0
Order By: Relevance
“…In addition, this process is energy intensive due to a distillation column and other equipment used to regenerate the glycol. The temperature swing adsorption (TSA) process using commercial adsorbents such as molecular sieves and alumina has also been used in the natural gas processing industry. ,,− Novel materials such as metal organic frameworks, SiO 2 composites, silver nanoparticles, and hierarchical porous zeolites were used as adsorbents to improve this adsorption process. These adsorbents, however, require high regeneration temperatures (250 °C and higher), which limits the application of biosorbents in this process because they decompose (pyrolysis) at high temperatures. Therefore, pressure swing adsorption (PSA), which is operated for adsorption at high pressure and desorption at low pressure, seems to be a better option due to lower operating temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, this process is energy intensive due to a distillation column and other equipment used to regenerate the glycol. The temperature swing adsorption (TSA) process using commercial adsorbents such as molecular sieves and alumina has also been used in the natural gas processing industry. ,,− Novel materials such as metal organic frameworks, SiO 2 composites, silver nanoparticles, and hierarchical porous zeolites were used as adsorbents to improve this adsorption process. These adsorbents, however, require high regeneration temperatures (250 °C and higher), which limits the application of biosorbents in this process because they decompose (pyrolysis) at high temperatures. Therefore, pressure swing adsorption (PSA), which is operated for adsorption at high pressure and desorption at low pressure, seems to be a better option due to lower operating temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…This was most recently shown for SiO 2-CaCl 2 composites where the spontaneous, multilayer mode of water adsorption was found to occur. 2 Moreover, an intensity of the multilayer adsorption appeared to be governed by the chloride content in a silica matrix.…”
Section: Theoretical Sectionmentioning
confidence: 99%
“…The recently developed hybrid porous materials composed of silica and a hygroscopic compound, e.g., calcium chloride or lithium bromide, appeared to be effective adsorbents of water vapor. So far these materials have been synthesized using the conventional two-step sol−gel procedure and tetraethoxysilane (TEOS) as silica precursor. However, in view of the process economy it may be of interest to test alternative cost-effective preparation variants (e.g., one-step) and the use of alternative, more easily available precursors.…”
Section: Introductionmentioning
confidence: 99%
“…19 An early study has demonstrated that the replacement of macroporous silica gel with aerogels and xerogels results in materials such as the composite CaCl2-xerogel that have exceptional equilibrium features for sorption desalination, improving the working capacity at the desalination operating conditions up to values ~1gwatergsorbent -1 . 20 Unfortunately, this investigation has been focused only on equilibrium measurements, lacking of the tests needed for the actual utilization of the material in real devices. Crystalline nanoporous materials have been also explored as materials for water-sorptive applications.…”
Section: Introductionmentioning
confidence: 99%
“…. 20 Unfortunately, this investigation has focused only on equilibrium measurements, lacking of the tests needed for the actual utilization of the material in real devices. Crystalline nanoporous materials have been also explored as materials for water-sorptive applications.…”
Section: Introductionmentioning
confidence: 99%